2022
DOI: 10.3389/fvets.2022.952922
|View full text |Cite
|
Sign up to set email alerts
|

Welfare issues and potential solutions for laying hens in free range and organic production systems: A review based on literature and interviews

Abstract: In free-range and organic production systems, hens can make choices according to their needs and desires, which is in accordance with welfare definitions. Nonetheless, health and behavioral problems are also encountered in these systems. The aim of this article was to identify welfare challenges observed in these production systems in the EU and the most promising solutions to overcome these challenges. It is based on a review of published literature and research projects complemented by interviews with expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 125 publications
0
20
0
Order By: Relevance
“…Having access to an outdoor area may also reduce the risk of heat and cold stress under certain circumstances. For instance, well‐shaded areas on the range may offer a favourable climate on hot days (Bonnefous et al., 2022) and draw hens out of the house, potentially reducing indoor temperatures. Similarly, range use may improve plumage condition which makes hens less susceptible to cold stress.…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Having access to an outdoor area may also reduce the risk of heat and cold stress under certain circumstances. For instance, well‐shaded areas on the range may offer a favourable climate on hot days (Bonnefous et al., 2022) and draw hens out of the house, potentially reducing indoor temperatures. Similarly, range use may improve plumage condition which makes hens less susceptible to cold stress.…”
Section: Assessmentmentioning
confidence: 99%
“…As the hens can choose to go out or to stay inside, the percentage of hens that use the range will affect any benefits that can be derived from outdoor access (whether these are benefits to the hens that choose to go outside themselves, or to those that stay in and experience a lower indoor stocking density due to other birds being outside). The variations in the use of the outdoor area between farms can be explained by climatic conditions, range design or stocking density, while intra‐flock differences appear to be related to personality and experience of the hens (Bonnefous et al., 2022). Older studies using direct observation reported relatively low use of the outdoor range (9–30% of the flock outdoors simultaneously (Zeltner and Hirt, 2003; Hegelund et al., 2005)).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review identified welfare issues in free range and organic laying hen flocks in Europe based on literature and expert interviews ( Bonnefous et al, 2022 ). The study highlighted the enhanced risk of bacterial, viral and parasitic infection in layer flocks with outdoor access.…”
Section: Discussionmentioning
confidence: 99%